2017
DOI: 10.4236/ajps.2017.810170
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Sensitivity of <i>Campomanesia adamantium</i> (Cambess.) O. Berg Seeds to Desiccation: Effects of Polyethylene Glycol and Abscisic Acid

Abstract: The Campomanesia adamantium is a threatened species from Brazil Savannah which seeds are desiccation-sensitive and do not withstand storage. This study aimed to reduce the sensitivity of Campomanesia adamantium seeds to desiccation using polyethylene glycol (PEG) and abscisic acid (ABA). Initially, seeds were subjected to PEG (0, −1.48, and −2.04 MPa) with or without ABA (100 μM) during 120 h, followed fast drying (silica gel) or slow drying (laboratory environment), at 20%, 15%, and 10% moisture content. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Gabirobeira is propagated sexually, however, the recalcitrance of its seeds hampers this process due to deterioration over time, resulting in a root protrusion rate of less than 50% (Dresch, Scalon, Masetto, & Mussury, 2014). Knowledge about the asexual propagation of this species is still incipient, but holds potential as a viable alternative for its entry into the consumer market and the preservation of the species it its natural state (Dresch, Masetto, Jeromini, & Scalon, 2017;Araújo & Souza, 2018;Oliveira, Silva, Costa Netto, Silva, & Silva, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Gabirobeira is propagated sexually, however, the recalcitrance of its seeds hampers this process due to deterioration over time, resulting in a root protrusion rate of less than 50% (Dresch, Scalon, Masetto, & Mussury, 2014). Knowledge about the asexual propagation of this species is still incipient, but holds potential as a viable alternative for its entry into the consumer market and the preservation of the species it its natural state (Dresch, Masetto, Jeromini, & Scalon, 2017;Araújo & Souza, 2018;Oliveira, Silva, Costa Netto, Silva, & Silva, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Since seeds of C. adamantium do not withstand storage due to their desiccation sensitivity, difficulties in maintaining them in seed banks and propagating cultivars are an ecologically and financially valid concern. Researchers have found that submitting C. adamantium seeds to a polyethene glycol (PEG) treatment without the increment of abscisic acid (ABA) followed by fast drying (silica gel) up to 15% of water content was able to stimulate protective mechanisms against damage caused by desiccation (Dresch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%